Matrizes e capelas do Ceará: circularidade e conexões atlânticas: arquitetura e artífices entre os sertões do Nordeste e Portugal (1700-1820) - Beserra, José Ramiro Teles (2019)
Colonial religious architecture in the state of Ceará is unknown and little studied, as it verifies easily in the lack of a bibliography emphasizing such typology. This gap is mostly due to prejudgment attributed to this countryside architecture by the official institutions for cultural heritage preservation that not find in it a faithful transposition of the exceptional and preestablished erudite standards, which leads to its marginalization within the national preservation policy. In fact, this architecture is hybrid and with a rare simplicity due to its contradictory synthesis of many factors such as social order, economy and geography. As it shall be seen, its singularity is related to two main genitive factors that give its own meaning: the men, ideas and their circulation patterns throughout the local, regional and Atlantic connections. And the transculturation of these ideas in a new land like means of technical, social and economic possibilities in the Northern countryside. In light of an inexistent bibliography and rarity of primary written sources, a set of edifications has been analyzed as an architectonic physical document and approached through an empirical observation basis. In this research, these constructions have been considered as vernacular objects reflecting predicative techniques and symbolic resignifications of the world vision and ideas that have migrated with colonizers and changing culture due to the need of adaptation in the new environments. Besides its importance as an innovative architectonic object, this colonial religious architecture has also participated as a key element in the expansion and consolidation of urbane networks in the countryside. To highlight such fact, an inventory of 50 edifications spread out in this territory has been produced, in which typical categories of analysis of architecture discipline were systemized. Thereby, the main objective is to insert this religious and colonial architecture of the Ceará in the general background of the Portuguese speaking people contributions, relating it to the idea of place, in which it has been gestated and transculturado; the Ceará countryside.